2016
DOI: 10.1371/journal.pone.0157698
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel HA/ZrO2-Based Porous Bioceramic Artificial Vertebral Body Combined with a rhBMP-2/Chitosan Slow-Release Hydrogel

Abstract: A new HA/ZrO2-based porous bioceramic artificial vertebral body (AVB), carried a recombinant human bone morphogenetic protein-2 (rhBMP-2)/chitosan slow-release hydrogel was prepared to repair vertebral bone defect in beagles. An ionic cross-linking was used to prepare the chitosan hydrogel (CS gel) as the rhBMP-2 slow-release carrier. The vertebral body defects were implanted with the rhBMP-2-loaded AVB in group A, or a non-drug-loaded AVB in group B, or autologous iliac in group C. The encapsulation rate of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Although studies in dogs, minipigs, sheep, and non-human primates, could provide a better insight into new bone formation and scaffold effectiveness thanks to the closer resemblance to the human bone, only studies employing rat and rabbit models were found to satisfy eligibility criteria, and were, therefore, included in the present systematic review [21,[27][28][29]126]. Even though after the first step of screening, studies in dogs, sheep, and pigs were included, the full-text analysis revealed that most of these studies did not meet the selection criteria due to a reduced sample size (n < 6 animals per group) or the non-critical dimensions of the bone defects [94,100,102,103,106]. Among the papers included, the most frequently used CSD model was the CSD in rat calvaria, which is one of the most commonly used animal models for evaluating bone healing [23,127].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies in dogs, minipigs, sheep, and non-human primates, could provide a better insight into new bone formation and scaffold effectiveness thanks to the closer resemblance to the human bone, only studies employing rat and rabbit models were found to satisfy eligibility criteria, and were, therefore, included in the present systematic review [21,[27][28][29]126]. Even though after the first step of screening, studies in dogs, sheep, and pigs were included, the full-text analysis revealed that most of these studies did not meet the selection criteria due to a reduced sample size (n < 6 animals per group) or the non-critical dimensions of the bone defects [94,100,102,103,106]. Among the papers included, the most frequently used CSD model was the CSD in rat calvaria, which is one of the most commonly used animal models for evaluating bone healing [23,127].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the BMP‐2 release rate is an important factor in inducing effective bone regeneration (Seo, Koh, & Song, ). Our previous study showed that 28% and 49% of recombinant human BMP‐2 was released on Days 1 and 3, respectively, after BMP‐2 was added into gelatin/chitosan slow‐release hydrogel and was then released slowly from Days 3 to 15, with a cumulative release of 74% by Day 12 and 77% by Day 15 (Shi et al, ). In the present study, loading of BMP‐2 in the gelatin/chitosan slow‐release hydrogel was performed using the technology of complex emulsion cross‐linking, thereby reducing the BMP‐2 release rate and improving its biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…by Day 12 and 77% by Day 15 (Shi et al, 2016). In the present study, loading of BMP-2 in the gelatin/chitosan slow-release hydrogel was performed using the technology of complex emulsion cross-linking, thereby reducing the BMP-2 release rate and improving its biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…79 In addition, zirconia/HA-based porous bioceramics loaded with recombinant human BMP-2 promote the repair of bony defect and facilitate bone growth in vivo, which might substitute the use of iliac bone grafts in routine clinical practice. 80 Taken together, zirconia-based scaffolds show good mechanical performances and biocompatibility and are promising biomaterials to be used in bone reconstruction needed in the treatment of load-bearing large bone defects.…”
Section: Osteogenic Scaffolds For Hard Tissue Engineeringmentioning
confidence: 99%